Pandangan Ekonomi Islam Terhadap Minat Beli Mahasiswa Sekolah Tinggi Ekonomi Manajemen Bisnis Islam Bandung Melalui Sistem Online Shop - Meriyani; Neng Cahya Komala (Economic Reviews Journal, 2024)
The porpose of this research is to determine Islamic views on buying interest in online shops. This type of research is a qualitative type of research using data collection methods in the form of observation, interviews and documentation. The techniques used for analysis are data reduction, data presentation and conclusions. The results of this research show that several informants or students who were interviewed were more interested in shopping at online shops than at markets and shops because there are various conveniences, they can save time and the prices are cheaper. The Islamic economic view regarding interest in buying from online shops is that doing business online is permitted as long as there is no injustice or the goods are defective as well as elements of usury and fraud. According to several informants or students who have been interviewed, it is legal to shop at an online shop as long as the goods are clear and there are no elements of usury or gharar in them, and there must be an agreement between both parties, namely between the buyer and the seller.